Pattern of adverse drug reactions reported at a tertiary care teaching hospital in Punjab - Punj, Vaishalee; Kumar, Rahat (International Journal of Basic & Clinical Pharmacology, 2019)
Background: This study was undertaken to characterize the pattern of adverse drug reactions (ADRs) reported through spontaneous reporting system at ADR reporting unit in a tertiary care teaching hospital (Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar). Methods: A prospective, observational study was conducted over one year between 1st July, 2013 and 30th June, 2014. The ADRs reported were from patients attending outpatient department (OPD) and in-patient department (IPD) of this hospital. Evaluation of the data was done for various parameters which included patient demographics, drug and ADR characteristics and outcome of the ADRs. Causality and severity assessment was done by WHO-UMC system and modified Hartwig and Siegel criteria. Results: A total of 202 ADRs which were reported over one year were evaluated. Overall ADRs were more common in females than in males (60.2% vs. 39.8%). Majority of the ADRs were reported from psychiatry department (50%). Most ADRs occurred due to antidepressant drugs (55.1%). Majority of the ADRs involved the central nervous system (25.24%). Upon causality and severity assessment, majority of the reports were rated as probable (57.42%) and mild (57.92%). None of the ADRs were severe or fatal. Conclusions: In conclusion, majority of the ADRs were reported by psychiatry department and occurred due to antidepressant drugs. Most of the ADRs were mild. This data reveals the need for regular spontaneous reporting by healthcare professionals of all specialties. This data also reveals the opportunities for interventions and policy initiatives to ensure safer use of drugs in future.